2012
DOI: 10.1002/app.36843
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of polycaprolactone nanofibers via forcespinning™ technology

Abstract: Among the myriad of methods for polymer nanofiber production, there are only a few methods that can produce submicron range fibers in bulk from melt or solution samples. The Forcespinning TM method allows a substantial increase in sample yield while simultaneously maintaining the integrity of uniform fibers in the nanometer range. The high production yield of such a method greatly reduces the time needed to produce bulk quantities of fibers which may be critical in many fields of research and industry, in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 24 publications
(24 reference statements)
7
88
0
1
Order By: Relevance
“…Electrostatic force makes the material stretched, when the surface tension is overcome, a jet is ejected from the spinneret, then the jet undergoes a spiral trajectory and finally the jet arrives the collector. Although there are many virtues to the electrospinning process, the low fiber production rates, high voltage (5kV~60kV), solvent limitations and so on make it unable to large scale commercial use [7][8][9][10]. In recent years, some progresses have been made to increase the production rate of electrospinning.…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic force makes the material stretched, when the surface tension is overcome, a jet is ejected from the spinneret, then the jet undergoes a spiral trajectory and finally the jet arrives the collector. Although there are many virtues to the electrospinning process, the low fiber production rates, high voltage (5kV~60kV), solvent limitations and so on make it unable to large scale commercial use [7][8][9][10]. In recent years, some progresses have been made to increase the production rate of electrospinning.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that a combination of these factors contributes to generating fibres with a range of fibre diameters significantly greater than the reported mean value. It has been previously reported that mean fibre diameter of centrifugal spun fibres decreases with spinning duration and it is proposed that a continuous machine would create a lower proportion of coarse fibres as the effects of acceleration and deceleration are minimised [15].…”
Section: Capillary Rheometrymentioning
confidence: 99%
“…This technique involves rotating polymer fluids at high speeds to induce jet formation and elongation without the need for external drawing, electrostatic forces or high velocity hot air [14]. It has been demonstrated that centrifugal spinning can readily produce fibres finer than 1 lm from a variety of polymer materials [14,15] from either thermoplastic liquid melts or solutions. Fibres have been produced from conventional thermoplastics such as nylon and polyester; speciality polymers such as polycaprolactone and poly(lactic acid); bismuth; ceramic materials; compounds of polypropylene and carbon nanotubes; compounds of poly(ethylene terephthalate) with graphene [13,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications and future research directions into nanofibers including RJS fibers are attributed to a few key areas of interest, namely filtration, 3 healthcare, environmental engineering, biotechnology, composites, 121 defense and security and the energy sectors. 143 Many researchers have started studies into RJS nanofibers driven by applications within specific sectors such as medicine, where fibers resemble cellular topographies 63 or are capable of targeted outcomes such as drug delivery. 68 Others have focused on using conjugated polymers in the RJS process for areas such as photovoltaic cells, light-emitting diodes, and biocompatible materials.…”
Section: Materials Used In Rotary Jet Spinningmentioning
confidence: 99%